Experimental Study on Early-Age Crack of Mass Concrete under the Controlled Temperature History - Nannan Shi; Jianshu Ouyang; Runxiao Zhang; Dahai Huang (Advances in Materials Science and Engineering)
Thermal deformation under restrained conditions often leads to early-age cracking and durability problems in mass concrete structures. It is crucial to monitor accurately the evolution of temperature and thermal stresses. In this paper, experimental studies using temperature stress testing machine (TSTM) are carried out to monitor the generated thermal cracking in mass concrete. Firstly, components and working principle of TSTM were introduced. Cracking temperatures and stress reserves are selected as the main cracking evaluation indicators of TSTM. Furthermore, effects of temperature controlling measures on concrete cracking were quantitatively studied, which consider the concrete placing temperature (before cooling) and cooling rates (after cooling). Moreover, the influence of reinforcement on early-age cracking has been quantitatively analyzed using the TSTM. The experimental results indicate that the crack probability of reinforced concrete (RC) is overestimated. Theoretical calculations proved that the internal stress can transfer from concrete to reinforcement due to creep effect. Finally, the experimental results indicate that the reinforcement can improve the crack resistance of concrete by nearly 30% in the TSTM tests, and the ultimate tensile strain of RC is approximately 105% higher than that of plain concrete with the same mix proportions.